Existence and convergence theorems for γ-hybrid set-valued mappings in hilbert spaces - Suthep Suantai (2018)
Copyright © 2015 Watam Press. In this paper, we define a new class of set-valued mappings in a Hilbert space, called -hybrid. We prove some fixed point theorems for mappings in this class. Finally, we establish weak convergence of modified SP-iteration to a fixed point of -hybrid set- valued mappings in Hilbert spaces. Our results extend many known recent results in the literature.